(untitled) (Proceedings of Southern Federal University. Philology, 2020)
Taking into account the achievements of modern Intermedia practices, the article analyzes Victor Slavkin’s one-act play «The Picture» (1982) in the context of the interaction of literature and painting. In connection with the recently published diary entries of the writer, the path from the design of the play to publication in the journal «Modern Drama» is traced. The genreforming function of ekphrasis is emphasized. The presence of the landscape on the wall of the room expands the boundaries of a single room, the dialogue of characters in front of the picture reveals the characters in a short time of action. The peculiarities of ekphrasis are manifested in contrasting images (artist Guest and engineer Boss), in the guest’s description of imaginary paintings, coloristic filling, appeal to the trends of Western European art, etc. The symbolic significance of ekphrasis in the dramatic action of Slavkin’s play is emphasized, and the connection between visual imagery and the philosophy of art is examined. Key words: ekphrasis, the image of the painter, Viktor Slavkin, «The Picture», «The Many-coloured Notebooks», Lev Shestov, the philosophy of art. DOI 10.18522/1995-0640-2020-3-151-159